Les grandes lignes de force de l’assurance responsabilité professionnelle au Canada - Tellier, Claude (Assurances, 1984)
The following is the text of a speech by Claude Tellier, Q.C., given on October 12, 1983 before the Society of Fellows of the Insurance Institute of Canada. The author gives his frank opinion on the practice of professional liability insurance in the United States and in Canada, looking at the various aspects of the problem. We set forth the text so that our readers can judge for themselves the pertinence of Mr. Tellier's comments and suggestions.